Kwestia pierwotności funkcji estetycznej muzyki w świetle znalezisk archeologicznych - Podlipniak, Piotr (Folia Praehistorica Posnaniensia, 2019)
Bony flutes dated back to around 43,000 years old are the clearest examples of musical instruments ever found. There are also other archeological artifacts related to the possible musical activity of Homo sapiens and Homo neanderthalensis, which are the subject of numerous controversies. Bearing in mind that singing is the simplest form of musical activity that does not need any tools, the beginning of music must have been much older than the first musical instruments. Due to the fact that the sonic results of prehistorical hominins’ musical activity have not been preserved, the question of the artistic nature of hominins’ music requires the ethological knowledge as well as archeological findings. One of the widely discussed ethological hypotheses concerning human proclivity to behave artistically is the idea of artification, which has been proposed by Ellen Dissanayake. This idea suggests that the source of the human proclivity for art is the species-specific predisposition of Homo sapiens to transform the mundane non-artistic phenomena into art. However, while in the case of visual arts, the archeological discoveries of prehistorical paintings are by themselves the proof of such transformation in order to recognize the aesthetic function of our ancestors’ sound expressions the interpretation of the archeological discoveries of musical instruments in a broader context seems to be indispensable. The main aim of this article is to indicate that communication that has led to social consolidation has been the primordial function of music. Only together with the accelerating cultural evolution that occurred at the end of the middle Paleolithic period, musical activity was transformed from a simple communicative tool into an aesthetic phenomenon. It is proposed that this transformation could have been possible thanks to the appearance of the proclivity to artification.